A Case Study of One Inclusive Recreation Course. Issue 1 (4th May 2022) - Theriault, Daniel
Abstract: Diversity and inclusion courses are common components of undergraduate leisure studies curricula. Although a body of diversity and inclusion content has been developed, few detailed course structures have been shared. I share the learning outcomes, course units, lecture topics, assigned readings, and key assignments from my inclusive recreation class in this essay. Lessons learned while teaching this course are also shared to facilitate both critique and utilization of these materials. Course materials are shared in the interest of inciting others to share their approach to diversity and inclusion courses so that a wider dialogue on what effective instruction of those courses looks like might begin. I close the essay with reflections and lingering questions on the teaching of diversity and inclusion in leisure studies.